PEMANFAATAN INFORMASI PERPUSTAKAAN OLEH PUSTAKAWAN - Delvalina Delvalina (Jurnal Imam Bonjol: Kajian Ilmu Informasi dan Perpustakaan, 2021)
The oldest and most well-established information professionals are librarians, archivists, and museum curators. If you want to expand, the information profession includes librarians, archivists, those who practice information science, information management, librarians with information development, record management, and documentation. In a broader definition, information includes visual objects and three-dimensional objects that are preserved because of the quality of the information, so the information profession includes curators in museums. So in this case the information officer handling external publicity and communication of a cooperative body is also included in the information profession.